Agricultural Incentives - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Incentives to agricultural production are continuously changing in response to shifts in both agricultural policies and agricultural prices. These shifts impact the production and consumption choices made by farmers and consumers, which in turn impact hunger and malnutrition, change labor markets, and shape the global picture on climate change. Historically, updated information and data on agricultural incentives has been widely scattered and largely inaccessible on a global scale. The Ag Incentives Consortium aims to change this by bringing together key international organizations to provide comparable incentives data in a single location. With web-based tools managed by IFPRI, the Consortium currently includes OECD, FAO-MAFAP, IDB, IFPRI, and the World Bank. Support is provided by the CGIAR Research Program on Policies, Institutions, and Markets (PIM). The tools provided by Ag Incentives allow users to visually compare data for nearly 60 countries and 70 products over 10 years. Users can also download data in CSV format to perform their own analyses. To find out more about the Consortium and available tools, visit the website at www.ag-incentives.org. For further information and any questions about our data, email us at info@ag-incentives.org.